The Effects of Servant Leadership, Occupational Commitment, and Work Engagement on Creativity of Teacher - Lindawati, Mega; Wulani, Fenika; Runtu, Julius (KINERJA, 2024)
This study identifies the influence of servant leadership on teacher creativity. We considered occupational commitment and work engagement as sequential mediators in the relationship between servant leadership and teacher creativity. This current study uses surveys by distributing questionnaires to teachers at the "X" education foundation in one of the cities in East Java. Hypothesis testing uses partial least squares-structural equation modeling (PLS-SEM). Our study shows that servant leadership does not directly enhance teacher creativity but rather through occupational commitment and work engagement. This finding contributed to the understanding that servant leadership influences teacher creativity through the sequential mediation of occupational commitment and work engagement. As an implication, the "X" educational foundation needs to choose principals who are able to act as servant leaders. In order to effectively increase teacher creativity, servant leaders must provide support and opportunities for teachers that will boost their commitment to their work. Teachers with high occupational commitment will be more engaged with their work, allowing them to become more creative. In addition, various employee management activities, such as training, recognition, and selecting effective school principals, are needed to increase teachers' commitment, engagement, and creativity.